Mechanical, biochemical, and morphological changes in the heart from chronic food-restricted rats - Okoshi, Marina Politi [UNESP]; Okoshi, Katashi [UNESP]; Dal Pai, V; Dal Pai-Silva, M.; Matsubara, Luiz Shiguero [UNESP]; Cicogna, Antonio Carlos [UNESP] (Natl Research Council Canada, 2001)
Food restriction (FR) has been shown to induce important morphological changes in rat myocardium. However, its influence on myocardial performance is not completely defined. We examined the effects of chronic FR on cardiac muscle function and morphology. Sixty-day-old Wistar-Kyoto rats were fed a control (C) or a restricted diet (daily intake reduced to 50% of the amount of food consumed by the control group) for 90 days. Myocardial performance was studied in isolated left ventricular (LV) papillary muscle. Fragments of the LV free wall were analysed by light microscopy, and the ultrastructure of the myocardium was examined in the LV papillary muscle. The myocardial collagen concentration was also evaluated. FR decreased body weight (BW) and LV weight (LVW); the LVW/BW ratio was higher in the restricted group (C, 1.86 +/- 0.17 mg/g; FR, 2.19 +/- 0.31 mg/g; p < 0.01). In the FR animals, the cardiac fibers were polymorphic, some of them were of small diameter and others presented lateral infoldings; the ultrastructural alterations were focal and included reduction of sarcoplasmic content, absence and (or) disorganization of myofilaments and Z line, numerous electron dense and polymorphic mitochondria, and deep infoldings of the plasma membrane. The hydroxyproline concentration was higher in the FR animals (p < 0.01). FR prolonged the contraction and relaxation time of the papillary muscle and did not change its ability to contract and shorten. In conclusion, although a 90-day period of FR caused striking myocardial ultrastructural alterations and increased the collagen concentration, it only minimally affected the mechanical function.
Keywords: diet; papillary muscle; undernutrition; myocardium; ultrastructure